1997
DOI: 10.1161/01.cir.95.6.1417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Viability by Use of 11 C-Acetate and Positron Emission Tomography

Abstract: After myocardial infarction, quantitative indexes of perfusion and oxidative metabolism from acetate PET indicate a critical threshold beyond which tissue is irreversibly injured. Findings support the use of blood flow as a marker of myocardial viability in chronic postinfarct patients with modestly reduced ejection fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…FDG is a well-established tracer of metabolism, and its uptake has been shown to be a sensitive marker of myocardial viability. [42][43][44] None of the atria in the present study demonstrated any abnormality or regional defect in FDG Figure 4. PET images of atria from a dog in which phenol was applied.…”
Section: Pet Imagingmentioning
confidence: 44%
“…FDG is a well-established tracer of metabolism, and its uptake has been shown to be a sensitive marker of myocardial viability. [42][43][44] None of the atria in the present study demonstrated any abnormality or regional defect in FDG Figure 4. PET images of atria from a dog in which phenol was applied.…”
Section: Pet Imagingmentioning
confidence: 44%
“…Otherwise, oxygen use ultimately falls below a critical threshold, and dysfunctional myocardium becomes unsalvageable. 43,44 Conversely, in cases of timely revascularization, regional contractile function and consequently mechanical efficiency may be restored, which in turn is accompanied by improved prognosis. 45 More recently, metabolic interventions with drugs that increase glucose metabolism in ischemic heart disease have demonstrated that this energetically more favorable circumstance also translates into improved systolic function and improved clinical outcome.…”
Section: Knaapen Et Al Noninvasive Assessment Of Myocardial Efficiencymentioning
confidence: 99%
“…Wolpers et al also determined threshold values for viability [89]. In contrast to other studies mentioned here, absolute MBF, derived from modelled acetate uptake rate and the Renkin-Crone equation from Armbrecht [33], was the best predictor of viability.…”
Section: Prediction Of Recovery Of Function By Acetate Clearancementioning
confidence: 54%
“…The acetate clearance and RPP were not significantly correlated in patients, whereas they were in volunteers (r=0.31 vs r=0. 89). This may have been due to the altered substrate availability in diabetic patients, with a significant effect on the work-MVO 2 relationship.…”
Section: Other Studiesmentioning
confidence: 99%